Antifouling agent, antifouling coating film and substrate with antifouling coating film
A copolymer-based antifouling agent effectively addresses the inadequacies of existing agents by providing superior stain resistance and odor reduction, ensuring effective protection against protein and microbial fouling without compromising material quality.
Patent Information
- Application Number
- JP2020565608
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-03-28
- Filing Date
- 2019-11-25
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2039-11-25
AI Technical Summary
Existing antifouling agents have insufficient efficacy against protein and microbial stains, and they often produce undesirable odors.
A copolymer composed of a polymerizable double bond-containing monomer with multiple hydroxyl groups and an alkyl (meth)acrylate monomer with 4 to 12 carbon atoms, which forms an antifouling agent with improved adhesion to surfaces and reduced odor.
The copolymer exhibits excellent antifouling effects against protein and microbial stains, maintaining a low odor profile and preserving the texture of treated materials.
Smart Images

Figure 0007603447000001 
Figure 0007603447000002 
Figure 0007603447000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an antifouling agent, an antifouling coating film, and a substrate with an antifouling coating film. [Background technology]
[0002] Stains caused by proteins, microorganisms, etc. cause problems such as impairing the aesthetic appearance of an article and being unsanitary. However, it is usually not easy to remove stains once they have adhered to an article. Therefore, various antifouling agents have been studied to prevent stains from adhering or to make it easy to remove stains even if they do adhere.
[0003] For example, Patent Document 1 proposes an antifouling agent containing an ether ester type nonionic surfactant or the like for the purpose of preventing staining of textile products, while Patent Document 2 proposes an antifouling agent containing an aromatic sulfonic acid-based formalin condensate for the purpose of preventing staining of hard surfaces such as toilet bowls. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2002-371466 A [Patent Document 2] JP 2007-99793 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, studies by the present inventors have revealed that the antifouling agent described in Patent Document 1 has insufficient antifouling effect against protein and microbial stains, and the antifouling agent described in Patent Document 2 has problems such as odor.
[0006] Therefore, an object of the present invention is to provide an antifouling agent which has an excellent antifouling effect against protein and microbial stains and has a sufficiently reduced odor, as well as an antifouling coating film and a substrate with an antifouling coating film which use the same. [Means for solving the problem]
[0007] In view of the above circumstances, the present inventors conducted extensive research and completed the inventions described below in [1] to [8]. [1] An antifouling agent comprising a copolymer having a structural unit derived from a polymerizable double bond-containing monomer having two or more hydroxyl groups, and a structural unit derived from an alkyl (meth)acrylate having an alkyl group with 4 to 12 carbon atoms. [2] The antifouling agent according to [1], wherein the polymerizable double bond-containing monomer having two or more hydroxyl groups includes a monomer represented by the following formula (I): [ka] (In formula (I), R 1 represents a hydrogen atom or a methyl group, and X represents an oxygen atom or an -NH- group. [3] The stain-proofing agent according to [1] or [2], which is for use in textile treatment. [4] The stain resistant agent according to [3], wherein the fiber is at least one selected from the group consisting of polyester, nylon and urethane. [5] The antifouling agent according to [1] or [2], which is used for treating wet items. [6] An antifouling coating film comprising the antifouling agent according to [1] or [2]. [7] A substrate having an antifouling coating film according to [6] on the substrate. [8] The substrate with an antifouling coating film according to [7], wherein the substrate is a ship, an underwater structure, a fishing net or fishing gear. Effect of the Invention
[0008] According to the present invention, it is possible to provide an antifouling agent which has an excellent antifouling effect against protein and microbial stains and has a sufficiently reduced odor, as well as an antifouling coating film and a substrate with an antifouling coating film which use the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, one embodiment of the present invention will be described in detail, but the present invention is not limited thereto. In this specification, the term "(meth)acrylic acid" means acrylic acid or methacrylic acid. The same applies to similar expressions such as "(meth)acrylate".
[0010] <Anti-fouling agent> The antifouling agent of the present embodiment contains a copolymer having a structural unit derived from a polymerizable double bond-containing monomer having two or more hydroxyl groups (hereinafter also referred to as "monomer (A)") and a structural unit derived from an alkyl (meth)acrylate (hereinafter also referred to as "monomer (B)") having an alkyl group with a carbon number of 4 to 12. Such an antifouling agent has an excellent antifouling effect against protein and microbial stains and has a sufficiently low odor.
[0011] The antifouling agent of the present embodiment will be described in detail below.
[0012] (copolymer) The monomer (A) is not particularly limited as long as it has a polymerizable double bond and two or more hydroxyl groups, but for example, a compound represented by the following formula (II) is preferable. The monomer (A) may be used alone or in combination of two or more kinds.
[0013] [ka] (In formula (II), R 1 is a hydrogen atom or a methyl group, R 2 represents an organic group having two or more hydroxyl groups.
[0014] In formula (II), R 2 is an organic group having two or more hydroxyl groups. Among them, -COOR 3 group, -OCOR 3 Group, -OR 3 group, -CONHR 3 group, -CH2OR 3 Group, -CH2OCOR 3 group, -CONHR3 Group, -CON(R 3 )2 or -NHCOR 3 Group(R 3 represents an organic group having two or more hydroxyl groups).
[0015] R 3 is an organic group having two or more hydroxyl groups, preferably an organic group having 1 to 30 carbon atoms and having two or more hydroxyl groups, and more preferably an organic group having 1 to 20 carbon atoms and having two or more hydroxyl groups. Examples of this organic group include an alkyl group having 1 to 20 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, a polyoxyalkylene group having 4 to 20 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms. Note that when R 3 If there are two or more R 3 may be the same or different. 3 may contain, for example, a halogen atom such as a fluorine atom or a chlorine atom, a nitrogen atom, or a functional group other than a hydroxyl group.
[0016] Examples of the monomer (A) include esters of polyhydric alcohols having three or more hydroxyl groups and (meth)acrylic acid, esters of sugars and (meth)acrylic acid, and esters of sugars having an amino group and (meth)acrylic acid. These esters may be prepared not only by esterification reaction, but also by transesterification reaction or ring-opening reaction of (meth)acrylic acid glycidyl ester.
[0017] Examples of polyhydric alcohols having three or more hydroxyl groups include glycerin, diglycerin, triglycerin, tetraglycerin, pentaglycerin, hexaglycerin, pentaerythritol, 1,2,6-hexanetriol, 2-hydroxymethyl-2-methyl-1,3-propanediol, and 2-ethyl-2-hydroxymethyl-1,3-propanediol. Examples of sugars include monosaccharides such as glucose, mannose, galactose, gulose, fructose, and D-ribose, as well as dimers and trimers of these monosaccharides, such as glucosides, galactosides, and fructosides derived from the monosaccharides. Examples of sugars having an amino group include D-glucosamine.
[0018] From the viewpoint of further improving the antifouling effect, the monomer (A) is more preferably a monomer represented by the following formula (I). [ka] (In formula (I), R 1 represents a hydrogen atom or a methyl group, and X represents an oxygen atom or an -NH- group.
[0019] The monomer represented by formula (I) is glycerol monoacrylate (R 1 = hydrogen atom, X = oxygen atom), glycerol monomethacrylate (R 1 = methyl group, X = oxygen atom), glycerol monoacrylamide (R 1 = hydrogen atom, X = -NH- group) or glycerol monomethacrylamide (R 1 = methyl group, X = -NH- group).
[0020] The structural unit derived from the monomer represented by formula (I) corresponds to the structural unit represented by the following formula (I'). [ka] (In formula (I'), R 1 and X has the same meaning as in formula (I).
[0021] The molecular weight of the monomer (A) is preferably 500 or less.
[0022] The monomer (A) is preferably a monomer synthesized by a method using a monomer having a 1,3-dioxolane structure as a raw material or intermediate. A copolymer polymerized using a monomer synthesized by using a monomer having a 1,3-dioxolane structure as a raw material or intermediate is preferable as an antifouling agent because it has good smoothness of a coating film and good texture when used as a fiber treatment agent.
[0023] From the viewpoint of further improving the antifouling effect, the content of the structural unit derived from the monomer (A) is preferably 5 to 90 mass%, more preferably 10 to 75 mass%, and even more preferably 15 to 60 mass%, based on the total amount of the copolymer.
[0024] The structural unit derived from the monomer (A) may be any structural unit having two or more hydroxyl groups in the copolymer. That is, it may be a structural unit polymerized using the monomer (A), or a structure having two or more hydroxyl groups may be introduced by modifying the polymer, for example by deprotecting the protecting groups after polymerizing a monomer in which two or more hydroxyl groups are protected by protecting groups.
[0025] Examples of the monomer (B) include n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, dodecyl (meth)acrylate, and stearyl (meth)acrylate. Among these, n-butyl (meth)acrylate is preferred. The monomer (B) may be used alone or in combination of two or more kinds.
[0026] From the viewpoint of further improving the antifouling effect, the content of the structural unit derived from the monomer (B) is preferably 10 to 95 mass%, more preferably 25 to 90 mass%, and even more preferably 40 to 85 mass%, based on the total amount of the copolymer.
[0027] The copolymer of the present embodiment may contain a structural unit derived from a monomer (C) that is neither the monomer (A) nor the monomer (B). Examples of the monomer (C) include (meth)acrylic acid; (meth)acrylic acid alkyl esters having an alkyl group of 1 to 3 carbon atoms, such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, and isopropyl (meth)acrylate; vinyl esters such as vinyl acetate and vinyl propionate; vinyl chloride, vinylidene chloride, and the like; olefins such as ethylene, propylene, butene, and isoprene; N-vinyl compounds such as N-vinylformamide and N-vinylacetamide; vinyl ethers such as methyl vinyl ether, ethyl vinyl ether, and propyl vinyl ether; and methylmaleimide. The monomer (C) may be used alone or in combination of two or more kinds.
[0028] The content of the structural unit derived from the monomer (C) is preferably 25% by mass or less, more preferably 20% by mass or less, and even more preferably 10% by mass or less, based on the total amount of the copolymer.
[0029] The glass transition temperature of the copolymer is preferably -10°C or lower. By setting the temperature at -10°C or lower, adhesion of proteins and microorganisms is particularly suppressed, and the antifouling effect is more excellent. The glass transition temperature can be measured by DSC (differential scanning calorimeter) or the like.
[0030] The copolymer can be produced by carrying out a polymerization reaction using the above-mentioned monomers appropriately selected. The preferred amounts of the monomers used in the polymerization reaction are the same as the preferred contents of the structural units derived from these monomers in the copolymer.
[0031] The polymerization reaction is preferably carried out in the presence of a polymerization initiator. Examples of suitable polymerization initiators include hydrogen peroxide; persulfates such as sodium persulfate, potassium persulfate, and ammonium persulfate; azo compounds such as dimethyl 2,2'-azobis(2-methylpropionate) and 2,2'-azobis(isobutyronitrile); and organic peroxides such as benzoyl peroxide, peracetic acid, and di-t-butyl peroxide. These polymerization initiators may be used alone or in the form of a mixture of two or more kinds. The amount of the polymerization initiator used is preferably 0.01 g or more and 10 g or less, and more preferably 0.1 g or more and 5 g or less, per mole of the amount of the monomer used in the polymerization reaction.
[0032] The polymerization reaction may be carried out without using a solvent, but it is preferable to use a solvent. Examples of the solvent include acetonitrile, tetrahydrofuran, dioxane, acetone, methyl ethyl ketone, methyl isobutyl ketone, methanol, ethanol, and isopropyl alcohol. These solvents may be used alone or in the form of a mixture of two or more kinds. The amount of the solvent used is preferably 40 to 250 parts by mass relative to 100 parts by mass of the monomer used in the polymerization reaction.
[0033] The polymerization reaction is usually preferably carried out at 0° C. or higher, and preferably at 150° C. or lower. More preferably, it is 40° C. or higher, even more preferably, it is 60° C. or higher, and particularly preferably, it is 80° C. or higher. Also, it is more preferably, 120° C. or lower, and even more preferably, it is 110° C. or lower. The polymerization temperature does not need to be kept almost constant all the time during the polymerization reaction, and may be changed (heated or cooled) once or more than twice. The polymerization reaction may be carried out under any of normal pressure, pressurized, and reduced pressure conditions.
[0034] In the above polymerization reaction, the monomers, polymerization initiator, etc. may be added to the reactor all at once or successively.
[0035] The method for producing the copolymer may include other steps in addition to the polymerization reaction step, such as an aging step, a neutralization step, a deactivation step of the polymerization initiator or the chain transfer agent, a dilution step, a drying step, a concentration step, and a purification step.
[0036] The copolymer of the present embodiment may be one that has been crosslinked using a crosslinking agent or the like, but is preferably a non-crosslinked (non-crosslinked) copolymer.
[0037] The antifouling agent of the present embodiment may contain only the above-mentioned copolymer, or may be used in combination with other components other than the above-mentioned copolymer.
[0038] In addition, from the viewpoint of improving the handling property, the antifouling agent of the present embodiment is preferably used as a solution by dissolving the above-mentioned copolymer in a solvent. As the solvent, for example, methanol, ethanol, toluene, ethyl acetate, tetrahydrofuran (THF), chloroform, acetone, isopropyl alcohol (IPA), acetonitrile, dimethylformamide (DMF), dimethyl sulfoxide (DMSO), etc. can be used. Among these, ethanol is preferable from the viewpoint of safety, etc.
[0039] When the antifouling agent is made into a solution, its concentration can be appropriately adjusted depending on the application method of the antifouling agent, and for example, the concentration of the above-mentioned copolymer in the solution can be 0.1 to 20 mass %.
[0040] <Applications of antifouling agents> The antifouling agent of the present embodiment has an excellent antifouling effect against protein and microbial stains and has a sufficiently low odor, so that it can be used for all articles to which sebum, starch, protein or microbial stains may adhere. Examples of protein stains include biological stains such as sweat, saliva, and blood, and food stains such as eggs and milk. Examples of microbial stains include stains caused by bacteria such as Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, and Streptococcus mutans, and molds that tend to grow around water such as black yeast-like fungus, phoma, sooty mold, and black mold.
[0041] The stainproofing agent of the present embodiment is preferably used as a stainproofing agent for treating fibers or water-related items.
[0042] When the stainproofing agent of the present embodiment is applied to the treatment of fibers, it has the effects of providing an excellent stainproofing effect, not causing problems of odor or toxicity, and not impairing the texture of the textile product.
[0043] The fibers to be treated with the stain resistant agent are not particularly limited, but examples thereof include polyesters such as polyethylene terephthalate, nylons, and urethanes. When treating fibers with the stain resistant agent, single fibers may be directly treated, or cloth-like fibers may be treated.
[0044] The method for treating the fibers with the stain-resistant agent is not particularly limited, but examples thereof include a method of immersing the fibers in a solution of the stain-resistant agent, a method of spraying the solution of the stain-resistant agent onto the fibers, and the like.
[0045] The suitable weight of the coating film (copolymer attached to the fiber) formed when the fiber is treated with the stain-resistant agent varies depending on the fiber used, but can be, for example, preferably 0.1 to 15 mg, more preferably 0.5 to 12 mg per gram of fiber. By setting the weight of the coating film formed when the fiber is treated with the stain-resistant agent within the above range, the influence on the texture of the textile product can be further reduced. Furthermore, since the stain-resistant agent of the present embodiment has excellent stain-resistant properties, even if the weight of the coating film per gram of fiber is small, it can exhibit a sufficient stain-resistant effect.
[0046] When the stain-proofing agent of this embodiment is applied to the treatment of wet items, it has an excellent stain-proofing effect and does not cause problems of odor or toxicity.
[0047] Examples of plumbing products to be treated with the stain-proofing agent include kitchen main parts such as sinks, workshops, and faucets; kitchen utensils such as draining baskets; bathroom main parts such as bathtubs, floors, and walls; bathroom utensils such as washbasins and bath chairs; brushes such as oral toothbrushes; washstands; toilets, etc. The material of the plumbing products is not particularly limited, but examples thereof include resins such as polyester resin, nylon resin, urethane resin, and acrylic resin; metals such as stainless steel; and ceramics.
[0048] The thickness of the coating film formed when treating wet items with the antifouling agent is not particularly limited, but can be, for example, 0.01 μm to 10 μm, preferably 0.1 μm to 5 μm, and more preferably 0.5 μm to 3 μm.
[0049] <Anti-fouling coating film> The antifouling coating film of this embodiment contains the above-mentioned antifouling agent. By forming the antifouling coating film of this embodiment on a substrate, the antifouling properties of the substrate can be improved. The antifouling coating film of this embodiment can be suitably applied to substrates that may come into contact with seawater, such as ships, underwater structures, fishing nets, fishing gear, and other articles. By applying the antifouling coating film of this embodiment to these substrates, it is possible to prevent fouling caused by microorganisms contained in seawater. EXAMPLES
[0050] The present invention will be described in more detail below by way of examples, but the present invention is not limited to these examples.
[0051] <Synthesis Example> [GLMA (glycerol monoacrylate)] A gas inlet tube, a thermometer, a cooling tube, and a T-shaped tube connected to a distillate receiver were attached to a reaction vessel containing a stirrer, and 230 g of methyl acrylate and 70 g of 2,2-dimethyl-1,3-dioxolane-4-methanol (DOM) were charged. The reaction solution was stirred while blowing in an oxygen / nitrogen mixed gas (oxygen concentration 7 vol%) through the gas inlet tube, and heating was started in an oil bath (bath temperature 110 ° C.). After water no longer appeared in the distillate, 4.5 g of titanium tetraisopropoxide was added to the reaction vessel to start the transesterification reaction. While the methanol produced was azeotropically distilled off with methyl acrylate, the area ratio of iPGLMA (isopropylidene glyceryl acrylate) / DOM was tracked by gas chromatography (GC) analysis. GC analysis 7 hours after the start of the reaction confirmed that the area ratio of iPGLMA / DOM exceeded 9 / 1, and the reaction was terminated and cooled to room temperature. In this way, iPGLMA, a monomer having a 1,3-dioxolane structure, was obtained as an intermediate in the synthesis of GLMA. 150 g of purified water and 300 g of ethyl acetate as an extraction solvent were added to the reaction solution and stirred for 10 minutes. The precipitate of titanium oxide produced by hydrolysis of titanium tetraisopropoxide was removed by suction filtration, and the filtrate was transferred to a separating funnel to separate the organic layer and the aqueous layer. The organic layer was washed twice with purified water, then transferred to a rotary evaporator, and the remaining methyl acrylate and low-boiling components were distilled off, obtaining 96 g of iPGLMA. A gas inlet tube was installed in a recovery flask containing a stirrer, and 160 ml of purified water and 80 g of iPGLMA were added and dissolved, and then 35 g of the solid acid catalyst Amberlyst 15Jwet (Organo Corporation), which had been immersed in water and then air-dried, was added. The reaction solution was stirred while blowing in an oxygen / nitrogen mixed gas (oxygen concentration 7 vol%) through the gas inlet tube, and the deprotection reaction was started at room temperature. The area ratio of GLMA / iPGLMA was tracked by GC analysis, and the reaction was terminated after 4 hours when it was confirmed that the area ratio exceeded 99 / 1. The filtrate obtained by filtering off the solid acid catalyst was washed with n-hexane to remove unreacted iPGLMA. The aqueous layer was concentrated under reduced pressure to obtain 53 g of the desired GLMA.
[0052] [Copolymer GB37] A gas inlet tube, a thermometer, and a cooling tube were attached to a reaction vessel containing a stirrer, and 12 g of glycerol monoacrylate (GLMA) and 28 g of butyl acrylate (BA) were charged as monomers, and 60 g of 1,4-dioxane as a solvent. Stirring and heating were started while flowing nitrogen gas. At an internal temperature of 80°C, 0.004 g of an azo radical polymerization initiator (manufactured by Wako Pure Chemical Industries, Ltd., product name: V-601) was added to start polymerization, and the reaction was carried out for 6 hours. The resulting reaction liquid was diluted with acetone and purified by pouring it into a large amount of hexane while stirring. The precipitate was dried under reduced pressure at 80°C for 4 hours in a vacuum dryer, obtaining a solid copolymer GB37. The weight average molecular weight of the resulting copolymer was 131,000. The glass transition temperature measured by DSC in accordance with JIS K7127 was -38.5°C.
[0053] [Copolymer GB46] A solid copolymer GB46 was obtained in the same manner as in Example 1, except that 16 g of glycerol monoacrylate (GLMA), 24 g of butyl acrylate (BA) were used as monomers, and 60 g of methyl ethyl ketone was used as a solvent. The weight average molecular weight of the obtained copolymer was 141,000. The glass transition temperature measured by DSC in accordance with JIS K7127 was -32.8°C.
[0054] [Copolymer GB55] A solid copolymer GB55 was obtained in the same manner as in Example 1, except that 20 g of glycerol monoacrylate (GLMA) and 20 g of butyl acrylate (BA) were used as monomers, and 60 g of ethanol was used as a solvent. The weight average molecular weight of the obtained copolymer was 57,000. The glass transition temperature measured by DSC in accordance with JIS K7127 was -26.8°C.
[0055] [Copolymer DB46] A gas inlet tube, a thermometer, and a cooling tube were attached to a reaction vessel containing a stirrer, and 4 g of 2,3-dihydroxypropylmethacrylamide (hereinafter also referred to as "DHPMA") as a monomer, 6 g of butyl acrylate (hereinafter also referred to as "BA"), 40 g of methanol as a solvent, and 0.02 g of an azo radical polymerization initiator (manufactured by Wako Pure Chemical Industries, Ltd., product name: V-65) were charged, and stirring and heating were started while flowing nitrogen gas. Polymerization was started at an internal temperature of 65°C, and the reaction was carried out for 6 hours. The resulting reaction solution was diluted with acetone and reprecipitated by pouring into a large amount of n-hexane with stirring. The precipitate was dried under reduced pressure at 40°C for 12 hours using a vacuum dryer to obtain a solid copolymer DB46. The weight-average molecular weight of the resulting copolymer was 51,000. The glass transition temperature measured by DSC in accordance with JIS K7127 was -27.2°C.
[0056] <Evaluation method> [Protein adhesion evaluation] Double-sided polymer-coated film (0.75 x 1 cm 2) were immersed in 3.6 mL of D-PBS(-) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., distributor code 045-29795) and primed at 37°C for 1 hour. The films were then immersed in 3.6 mL of the various protein solutions (1 mg / mL) shown below at 37°C for 1 hour. The films were then pipetted 10 times in PBS(-) in a reservoir, and this was repeated 5 times. Next, 10 films were placed in each 1.5 mL tube (manufactured by WATSON: ProKeep Protein Low Adhesion, product number: PK15C-500), and 1.2 mL of 1% SDS aqueous solution (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., distributor code 191-07145) was added to each tube, and the proteins were washed out by stirring at 37°C for 1 hour. After that, impurities were removed and proteins were concentrated by the chloroform / methanol method. The samples were resuspended in 50 μL of PBS(-) and 50 μL of 2× sample buffer (Fujifilm Wako Pure Chemical Industries, Ltd., distributor code 193-11032), reduced at 98°C for 5 minutes, and then subjected to SDS-PAGE electrophoresis (Laemmli method) (ATTO e-PAGEL, model ER 520L). After staining with SYPRO Ruby (Thermo Fisher Scientific, product number S12000), the samples were imaged using an imaging device (Bio-Rad, ChemiDoc TM Densitometric quantitative evaluation based on molecular weight was performed using the densitometric densitometry (Denver Touch) to measure the amount of protein adhesion. The amount of protein adhesion was evaluated by taking the amount of protein adhesion in the case of using the PS-coated film produced in Comparative Example 1 as 100%. (Various protein solutions) Albumin, human, plant expressed recombinant: Manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., distributor code 018-21541 Fibrinogen, from human plasma: Aldrich, product number F3879-250MG Fibronectin, from human plasma: Aldrich, product number F2006-1MG Gamma globulin, from human plasma: Manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., distributor code 075-06691 Lysozyme, human, recombinant (plant expressed): Manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., distributor code 189-02064 Myoglobin Salt Free, Horse Origin: Made by Nacalai Tesque, product code 23550-74 Trypsin inhibitor, soy: Manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., distributor code 202-20123
[0057] [Evaluation of microbial adhesion] The following strains were used. A frozen preserved strain was inoculated into 5 mL of medium in a culture test tube, and the culture was restored at the specified temperature while stirring at 300 rpm (shaking culture machine: Takasaki Scientific Instruments Co., Ltd., TXY-16R-3F), after which subculture (20 mL) was carried out for 18 hours. The cells were then collected by centrifugation at 5,000 x g for 5 minutes, after which the supernatant was removed and the plate was washed with 15 mL of PBS(-) or 0.85% NaCl aqueous solution. This washing process was carried out twice in total. The washed bacterial solution was placed in a 6-well microplate (IWAKI product code 3810-006) at 1 x 10 9 The concentration of cells / mL was adjusted and 3 mL was added to each well. 2 The polymer-coated film on each side was placed in the well and left to stand at a specified temperature for 1 hour. After that, the bacterial solution was removed from the well using a pipette, and 4 mL of PBS(-) or 0.85% NaCl aqueous solution was added and gently pipetted to rinse. This was repeated twice. The film was transferred to a separately prepared 6-well microplate, and 3 mL of 2.5% glutaraldehyde aqueous solution (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., distributor code 072-02262, diluted with PBS(-) or 0.85% NaCl aqueous solution) was added, and the film was left to stand at room temperature for 2.5 hours to immobilize it. Next, 5 mL of PBS(-) or 0.85% NaCl aqueous solution was added to the well and pipetted 10 times, after which the liquid was removed. Similarly, washing was performed twice with 5 mL of distilled water. Then, freeze-drying was performed to dehydrate it. The central part of the film was 0.75 x 0.75 cm 2The four sides were cut and placed on an SEM stage and gold was evaporated (JEOL, Smart Coater). The entire film was observed with an SEM (JEOL, JSM7600F), and five average points were photographed. The surface coverage of bacteria was calculated using ImageJ software for the obtained SEM photographs, and the amount of microbial adhesion was calculated. The amount of microbial adhesion when the PS-coated film produced in Comparative Example 1 was used was set as 100% for comparative evaluation. (Strain / Medium / Culture Temperature) Pseudomonas putida ATCC700801 strain / Trypticase Soy medium / 30℃ Streptococcusmutans NBRC13955 strain / BHI medium / 37℃ Staphylococcus aureus NBRC12732 strain / BHI medium / 37℃ Pseudomonas aeruginosa NBRC13275 strain / LB medium / 37℃
[0058] [Texture evaluation] The two types of fabric used for the evaluation were Shikisen PET (Fabric 1) and the Japanese Standards Association test white PET (Fabric 2). 2 The four pieces of cloth 1 and cloth 2 were soaked in a test solution with a solid content of 1%, and then wrung out with a mangle (manufactured by Daiei Kagaku Seiki Seisakusho). The amount of test solution remaining in the cloth was calculated from the weight change before and after the soaking, and the weight of the impregnated polymer (copolymer) was calculated from the polymer concentration of the test solution. After the soaked cloth was thoroughly dried, it was subjected to a sensory evaluation by 10 panelists according to the following criteria, and the average score was shown. <Score> 5 points: Softer texture than the target fabric 4 points: The fabric has a slightly softer texture than the target fabric. 3 points: The texture is the same as the target fabric 2 points: The texture is slightly harder than the target fabric. 1 point: The texture is significantly harder than the target fabric.
[0059] [Odor evaluation] The evaluation sample was coated on both sides to produce an evaluation film, which was then cut into A4 size and placed in a brown envelope and left overnight, after which the envelope was opened and the odor trapped inside was evaluated. The odor was evaluated by five expert panelists using the six-level odor intensity rating method shown in Table 1, and the obtained intensity was expressed as the average value (rounded off) of the five panelists. <Odor Intensity> 5 points: Odorless. 4 points: The smell is just detectable. 3 points: The smell is so weak that you can tell what it is. 2 points: The odor is easily detectable. 1 point: Strong odor. 0: Very strong odor.
[0060] [Anti-fouling coating film evaluation] A glass tube with an inner diameter of 5 mm and a length of 100 mm had a sample coating formed on its inner surface. 200 ml of seawater collected from Koshien Beach in Nishinomiya City, Hyogo Prefecture, was circulated through the tube for two months, after which it was dried at room temperature for one day and the state of dirt on the inner surface was visually evaluated. [Score] 5 points: The same transparency as the original state. 4 points: Compared to the initial state, the transparency has decreased slightly, but there are no stains. 3 points: Compared to the original state, the transparency has decreased slightly and there are stains in places. 2 points: Compared to the initial state, transparency has decreased slightly and there are many stains. 1 point: Compared to the initial state, the water has become cloudy and less transparent overall.
[0061] <Examples 1 to 4> Using a spin coater (MIKASA CO.LTD., SPIN COATER 1H-D7), 1 (w / w)% solutions of copolymers GB37, GB46, GB55, and DB46, each diluted with ethanol, were dropped onto an easily adhesive PET film (TORAY, Lumirror T60), and the film was air-dried. This was done on both sides to prepare double-sided polymer-coated films. Protein adsorption was evaluated using the films prepared. The results are shown in Table 1.
[0062] <Comparative Example 1> Using a spin coater (MIKASA CO.LTD., SPIN COATER 1H-D7), a 1 (w / w)% solution of polystyrene (PS; Aldrich, product number 441147-1KG) was dropped onto an easily adhesive PET film (Toray, Lumirror T60) and air-dried. This was repeated on both sides to produce a double-sided polymer-coated film (PS-coated film). Protein adsorption was evaluated using the film produced. The results are shown in Table 1.
[0063] [Table 1] From the above examples, it is clear that the antifouling agent of the present invention has an excellent effect of inhibiting protein adhesion.
[0064] <Examples 5 to 8> Microbial adhesion evaluation was carried out using the double-sided polymer-coated films produced in Examples 1 to 4. The results are shown in Table 2.
[0065] <Comparative Example 2> Microbial adhesion evaluation was carried out using the PS-coated film produced in Comparative Example 1. The results are shown in Table 2.
[0066] [Table 2] From the above examples, it is clear that the antifouling agent of the present invention has an excellent effect of inhibiting adhesion of bacteria.
[0067] <Examples 9 to 12> Copolymers GB37, GB46, GB55, and DB46 were each diluted with ethanol to prepare 1 (w / w)% ethanol solutions. Shikisensha PET (cloth 1) and Japan Standards Association test attachment white cloth PET (cloth 2) were immersed in the resulting ethanol solutions, respectively, and the liquid was removed using a mangle (manufactured by Daiei Kagaku Seiki Seisakusho) and then air-dried. Then, texture evaluation was performed. The results are shown in Table 3. [Table 3]
[0068] <Examples 13 to 16> Copolymers GB37, GB46, GB55, and DB46 were each diluted with ethanol to prepare ethanol solutions with concentrations of 10 ppm and 10,000 ppm. The odor evaluation was carried out using double-sided coated films prepared using each ethanol solution as evaluation films, and the results are shown in Table 4.
[0069] <Comparative Examples 3 to 5> Aromatic sulfonate formalin condensate, naphthalene sulfonate formalin condensate (Labelin FP: manufactured by Daiichi Kogyo Seiyaku), melamine sulfonate formalin condensate (Labelin FP: manufactured by Daiichi Kogyo Seiyaku), and fluorine compound, perfluoroalkyl ethylene oxide adduct (Unidyne DS-401: manufactured by Daikin Industries), were each diluted with ethanol to prepare ethanol solutions with concentrations of 10 ppm and 10,000 ppm. The results of odor evaluation using double-sided coated films made using each ethanol solution as evaluation films are shown in Table 4.
[0070] [Table 4]
[0071] <Examples 17 to 20> Copolymers GB37, GB46, GB55, and DB46 were each diluted with ethanol to prepare a 1 (w / w)% ethanol solution. A glass tube with an inner diameter of 5 mm and a length of 100 mm was filled with the obtained ethanol solution, and then the solution was drained and dried at room temperature for 60 minutes. The same operation was repeated once more to coat the inner surface of the glass tube with the polymer. The glass tube was connected to a circulation pump and a container containing 200 ml of seawater with a silicone rubber tube, and seawater was passed through and circulated through the glass tube for two months to evaluate the antifouling coating film. The results are shown in Table 5.
[0072] <Comparative Example 6> The inner surface of the glass tube was coated with polystyrene in the same manner as in Examples 17 to 20, except that the polymer solution filled in the glass tube was a 1 (w / w)% acetone solution of polystyrene, and the antifouling coating film was evaluated. The results are shown in Table 5.
[0073] <Comparative Example 7> The inner surface of the glass tube was coated with polyvinyl alcohol in the same manner as in Examples 17 to 20, except that the polymer solution filled in the glass tube was a 1 (w / w)% aqueous solution of polyvinyl alcohol, and the antifouling coating film was evaluated. The results are shown in Table 5.
[0074] [Table 5] From the above examples, it is clear that the antifouling agent of the present invention exhibits excellent antifouling properties even against fouling caused by microorganisms contained in seawater.
Claims
1. A copolymer having a structural unit derived from a polymerizable double bond-containing monomer having two or more hydroxyl groups and a structural unit derived from an alkyl (meth)acrylate having an alkyl group having 4 to 12 carbon atoms (wherein the copolymer is represented by the following formula (A): 【Chemistry 1】 [In the formula, R 2 , R 3 and R 4 are the same or different groups and each represents a hydrogen atom, an alkyl group or a hydroxyalkyl group having 1 to 6 carbon atoms, n represents an integer of 1 to 4, and * represents a bond.] (excluding those having a phosphorylcholine-like group represented by the formula: The polymerizable double bond-containing monomer having two or more hydroxyl groups is represented by the following formula (I): 【Chemistry 2】 (In formula (I), R 1 represents a hydrogen atom or a methyl group, and X represents an oxygen atom or an --NH-- group.) The monomer is represented by A stain-proofing agent for treating wet items or fibers (excluding those applied to medical devices), in which the content of structural units derived from a polymerizable double bond-containing monomer having two or more hydroxyl groups is 10 to 75 mass% based on the total amount of the copolymer, and the content of structural units derived from an alkyl (meth)acrylate having an alkyl group with 4 to 12 carbon atoms is 25 to 90 mass% based on the total amount of the copolymer.
2. 2. The stainproofing agent according to claim 1, which is a stainproofing agent for treating fibers, and the fibers are at least one type selected from the group consisting of polyester, nylon and urethane.
3. 3. An antifouling coating film for treating water-related items or textiles (excluding those applied to medical equipment) comprising the antifouling agent according to claim 1 or 2.
4. A fiber having the antifouling coating film according to claim 3 on the fiber (excluding those for medical devices).
5. A water-related product (excluding medical equipment) having the antifouling coating film according to claim 3 on a substrate.
6. The water-related product with an antifouling coating film according to claim 5, wherein the substrate is a ship, an underwater structure, a fishing net, or a fishing gear.
Citation Information
Patent Citations
Fiber treating agent, method for treating, and treated fiber
JP2002348778A
Composition of antifouling agent and antifouling agent
JP2002371466A
Antifouling agent for hard surface washable by water
JP2007099793A
Fluorosilicone dispersion and fluorine-containing silicon-containing surface treatment agent
JP2011516617A
Monomer composition for polymer for medical supply, and polymer for medical supply
JP2017101162A
